The Effect of Google Meet in Literal Listening Class for Students of English Education Study Program - Ramadhan, Sahrul; Lestari, Lesta; Rizqy, M; Mega, Iful Rahmawati (English Education Department, 2021)
Literal Listening is one of the compulsory courses in English Education. We are required to be able to understand at least 60 – 70 percent of what is being discussed and what is being reported by native speakers. Considering the decision of The Ministry of Education and Culture in Indonesia due to Covid- 19 pandemic that learning is carried online. Regarding that, several lecturers in the English Education Study Program chose to use the virtual technology in Google meet in order to keep the students engaged in Learning Process. This motivated the researcher to examine The Effect of Google Meet in Literal Listening Class for Second Semester Students of English Education Study Program. This research aims to know how the effectiveness of using google meets in Literal listening learning process and what the advantages and the weaknesses of using Google meet. The method used in this research is qualitative descriptive and used questionnaires to students and interview the lecturer as the subject for this research. The finding of this research is that the motivation of students did not improve. Thus, the lecturer needs to use another technology to support Google meet in order to go to full potential of using it.